Transformation Technology: the Impact of Robotics on Effective Production and Efficiency in Business - Suryanto Wiganepdo Soegoto; Arjuna Rizaldi; Mochamad Nurul Imam (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This research examined how robotics influences business operations, not only by improving efficiency and productivity, but also by pushing for changes in organizational structure, adjusting strategic plans, and supporting policy-making processes. Although previous research has revealed the operational benefits of robotics, such as higher productivity, lower costs, and improved safety, most research results view robotics primarily as a tool for performance improvement and pay less attention to its wider implications for companies. To close this gap, we conducted a PRISMA-based systematic literature review of freely accessible articles in English and Indonesian published between 2020 and 2025, sourced from Google Scholar. The studies included were those examining the impact of robotics on business operations, productivity, or organisational transformation within a business context. Articles not related to a business context, duplicate records, and studies without access to the full text were excluded. Of the 100 initial records, 71 were selected, 29 were assessed for eligibility, and 20 articles were included for qualitative analysis. The results of the research show that robotics boosts productivity through process automation, operational efficiency, and data-driven decision-making. These benefits not only speed up the production process and reduce costs, but also help companies develop strategies and improve the efficiency of organisational management. Unlike previous research, which focused more on operational and technological aspects, this study shows that robotics also plays a role in supporting organisational change. Robotics not only improves work efficiency, but also helps companies manage resources, formulate strategies and make more accurate decisions based on the data at their disposal. Keywords: Robotics; Business Transformation; Operational Efficiency; Effective Production; Digital Era